Association of the Triglyceride-Glucose Index and Obesity Indicators with Multiple Chronic Diseases: A Longitudinal Cohort Study Based on CHARLS - Lan Y; Qi G; Li B; Sooranna SR; Chen D; Rao W; Lin Y; Pang Y (Journal of Multidisciplinary Healthcare)
Yincai Lan,1,* Guangzi Qi,1,* Boya Li,1 Suren Rao Sooranna,2 Dongshun Chen,3 Wenlian Rao,3 Yinxia Lin,1 Yaqin Pang4– 7 1School of Public Health, Youjiang Medical University for Nationalities, Baise, Guangxi, 533000, People’s Republic of China; 2Life science and clinical research center, Youjiang Medical University for Nationalities, Baise 533000, Guangxi, China and Department of metabolism, digestion and reproduction, Imperial College London, Chelsea & Westminster Hospital, London, SW10 9NH, UK; 3School of Basic Medicine, Youjiang Medical University for Nationalities, Baise, Guangxi, 533000, People’s Republic of China; 4School of Medical Laboratory Medicine, Youjiang Medical University for Nationalities, Baise, Guangxi, 533000, People’s Republic of China; 5Key Laboratory of Environmental and Population Health Research, Ecological Aluminum Industrial Base of Guangxi Universities, Baise, Guangxi, 533000, People’s Republic of China; 6Key Laboratory for Environmental Pollution and Health Risk Assessment, Youjiang Medical University for Nationalities, Baise, Guangxi, 533000, People’s Republic of China; 7Modern Industrial College of Biomedicine and Great Health, Youjiang Medical University for Nationalities, Baise, Guangxi, 533000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yinxia Lin; Yaqin Pang, Email lin1837731@163.com; pangyaqin@126.comObjective: To explore the relationship between triglyceride glucose (TyG) and the obesity combined indexes and the occurrence of multiple chronic diseases (MCD), which will help to provide a basis for the prevention and treatment of this condition.Methods: 3037 participants in the China Health and Retirement Longitudinal Study, which was conducted from 2011 to 2015 were selected for this study. They were divided into four groups (Q1, Q2, Q3, Q4) based on the quartiles of TyG, TyG-BMI, TyGWC and TyGWHtR in the baseline data. A Cox proportional hazard model was used to analyze the risk of MCD associated with TyG and its obesity-related combined indicators. Dose-response relationships were analyzed using restricted cubic spline regression, and the predictive ability for detection of MCD was analyzed using ROC curve.Results: At the end of the follow-up in 2015, 473 new cases of MCD were observed among the study population, with an incidence rate of 15.6%. After adjusting for confounding factors, the risk of MCD significantly increased in the Q4 TyG, TyG-BMI, TyG-WC and TyG-WHtR index groups compared to the Q1 groups (p< 0.001 in all cases). A linear dose-response relationship was observed between the TyG index and the risk of MCD, indicating increased risks of CKD with higher TyG indexes. However, the TyG-BMI, TyG-WC and TyG-WHtR indexes exhibited nonlinear dose-response relationships with the risk of MCD (P-nonlinearity < 0.0001 in all cases), indicating higher indexes were associated with higher risks of MCD. The areas under the ROC curves for the Cox regression models of TyG, TyG-BMI, TyG-WC and TyG-WHtR indices were 0.610, 0.590, 0.590 and 0.607, respectively.Conclusion: The TyG, TyG-BMI, TyG-WC and TyG-WHtR indexes were found to be positively correlated with increased risk of developing MCD. Measurements and regulation of these indexes can be used to prevent and control the occurrence of MCD.Keywords: triglycerides-glucose, multiple chronic diseases, chronic disease comorbidity, CHARLS